The Relationship Of Early Supplementary Foods (Mp-Asi) On The Growth Of Infants 0-6 Months In The Jannah Clinic - Nurdiana Manurung; Rizky Andriani Bakara (Science Midwifery, 2019)
Providing complementary foods for breast milk should be given regularly. The thickness of the food and the amount must be adjusted to the skills and readiness of the baby in receiving food. The purpose of this study was to determine the relationship of early complementary feeding (MP-ASI) to the growth of infants 0-6 months at the Jannah Clinic in 2019. This research method used analytical observation with a cross sectional approach. The population in this study were all mothers who had babies 0-6 months at Jannah Clinic as many as 35 people. The sampling technique was total sampling, namely all mothers who had babies 0-6 months at the Jannah Clinic as many as 35 people. The results of the analysis showed that from 35 mothers who had babies 0-1 years, the majority of babies aged 6 months were 12 people (35%) and a minority of babies aged 2 months was 1 person (3%). Distribution based on the majority of abnormal weight gain as many as 20 people (57%). Distribution based on complementary feeding (MP-ASI) the majority on time as many as 19 people (54%). The results of the Chi-Square test obtained a value of = 0.000, this means that the p-value is smaller than (0.05), which means that there is a relationship between early complementary feeding (MP-ASI) on the growth of infants 0-6 months. It is hoped that health workers will provide counseling about MP-ASI, so that mothers who have babies 0-6 months only give breast milk, and babies >6 months are only given MP-ASI. 000, this means that the p value is smaller than (0.05) which means that there is a relationship between early complementary feeding (MP-ASI) on the growth of infants 0-6 months. It is hoped that health workers will provide counseling about MP-ASI, so that mothers who have babies 0-6 months only give breast milk, and babies >6 months are only given MP-ASI. 000, this means that the p value is smaller than (0.05) which means that there is a relationship between early complementary feeding (MP-ASI) on the growth of infants 0-6 months. It is hoped that health workers will provide counseling about MP-ASI, so that mothers who have babies 0-6 months only give breast milk, and babies >6 months are only given MP-ASI.